The sound of home? Some thoughts on how the radio voice anchors, contains and sometimes pierces. (1st April 2013) - Karpf, Anne
This article argues that, while psychoanalytic theory has been valuably employed by television, film and cultural studies, there has been no comparable 'psychoanalytic turn' in radio studies. It suggests that the concept of 'containment', as developed variously by Wilfred Bion and Esther Bick, might go some way to explain the powerful role that the voice of the radio presenter can play in the regular listener's internal world, with the capacity both to 'hold' the listener together, and to transform overwhelming fears into more manageable feelings. It argues that the disembodied radio voice does this partly because it recalls the prenatal power of the maternal voice, and partly through the temporal order that regular radio voices impose on the internal and external world. Both World War II British radio catchphrases and Roosevelt's fireside chats are discussed in relation to their containment function. The article also explores the radio as a transitional space, as defined by Donald Winnicott, through which it can constitute listeners into an 'imagined community'. It ends by reflecting on the impact of the angry voice of the 'shock jock', which, it suggests, amplifies rather than contains overwhelming feelings.